THE DEVELOPMENT OF UKRAINIAN PEDAGOGICAL SCIENCE: NEW CHALANGES, TASKS AND PROSPECTS - Живага, О. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article is analysed the state of ukrainian pedagogical science and education after the proclamation of independence of Ukraine and are determined main tasks, prospects and problems of their development in ХХІ century. It is also characterized here the activity of establishments where pedagogical and scientific-pedagogical workers are prepared.